2004
DOI: 10.1097/00129492-200405000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Degree of Modiolar Coiling, Electrical Thresholds, and Speech Perception After Cochlear Implantation

Abstract: The degree of coiling of a modiolar hugging electrode array was not directly correlated with the level of electrical thresholds or postoperative speech perception outcome measures. Appearance of coil tightness on postoperative radiographs could reflect either differences in array placement or intrinsic variations in cochlear anatomy, and variations in speech perception performance can be influenced by other factors, including length of deafness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 8 publications
0
27
1
5
Order By: Relevance
“…Furthermore, the studies in which perimodiolar arrays were compared with straight (lateral) arrays did not demonstrate an unequivocal correlation between the electrode-to-modiolar distance and the levels. Some studies showed that electrodes positioned perimodiolarly were associated with lower levels [Saunders et al, 2002], whereas others did not find such an effect for the distance to the modiolus [Huang et al, 2006;Long et al, 2014;Marrinan et al, 2004;van der Beek et al, 2005]. Additionally, at most a trend but no significant correlation was found between the distance to the modiolus and word score in our study.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, the studies in which perimodiolar arrays were compared with straight (lateral) arrays did not demonstrate an unequivocal correlation between the electrode-to-modiolar distance and the levels. Some studies showed that electrodes positioned perimodiolarly were associated with lower levels [Saunders et al, 2002], whereas others did not find such an effect for the distance to the modiolus [Huang et al, 2006;Long et al, 2014;Marrinan et al, 2004;van der Beek et al, 2005]. Additionally, at most a trend but no significant correlation was found between the distance to the modiolus and word score in our study.…”
Section: Discussioncontrasting
confidence: 90%
“…However, although Saunders et al [2002] showed that perimodiolar-designed electrode arrays decreased the T-and M-levels, the dynamic range (DR) did not increase as predicted. Additionally, others could not confirm that perimodiolar approximation led to lower T-levels [Huang et al, 2006;Long et al, 2014;Marrinan et al, 2004;van der Beek et al, 2005]. Kawano et al [1998], however, showed a correlation between the distance from the electrode to Rosenthal's canal using histological spec-imens and the level profile.…”
Section: Introductionmentioning
confidence: 99%
“…How these changes will relate to speech perception measures is unknown at present. One study (Marrinan et al, 2004) found no correlation between the tightness of coiling, as measured radiographically, and speech perception outcomes in a group of 28 adults. Because of the great variability among implant recipients, however, it will be difficult to fully assess outcomes with the newer electrode until larger numbers of subjects have been implanted and evaluated psychophysically.…”
Section: The Significance Of Modiolar Proximity and Insertion Depthmentioning
confidence: 99%
“…Our previous study using the Nucleus Contour (RCS) electrode inserted using the standard technique did not show a significant correlation between threshold values and degree of angular insertion, but there was a trend toward lower thresholds in the tight angular insertion (16). In addition, there was no correlation between degree of insertion and speech perception results.…”
mentioning
confidence: 91%